Using Constructivist Approach to Enhance Understanding of Mole Concept among Second Year Students in Chemistry at Adobewura Senior High School in Ashanti Region, Ghana - Baah, Kennedy Ameyaw; Owusu Ansah, Frank; Amoako, Stephen Kwame; Boachie, Solomon; Kwarteng, Christian (International Journal of Scientific Research and Management (IJSRM), 2020)
The aim of the research was to use constructivist approach to enhance performance of second year elective science students of Adobewura in mole concept. In order to achieve this, the researcher employed the following research questions; What methods do teachers use to teach mole concept and to what extent can constructivist approach be used to help students understand mole concept. Action research was used since action research is a way of assessing result while operating. Purposive sampling was used to select 30 students for the study. Data were collected through tests (pre-intervention and post-intervention tests). The scores of the pre and post intervention tests were compared and result analyzed. The analyzed results indicated that students’ performance had improved remarkably after the implementation of all the intervention. For instance, when the researcher implemented the demonstration techniques, 23 students scored marks within 41-90 representing 76.67% while 23.33% scored between 41-30. No student scored marks less than 30 marks.  Based on the findings of the study, it can be concluded that there are a lot of performance enhancements in using constructivist approach in teaching and learning mole concept at Adobewura SHS since it improves conceptual understanding and also there is a positive effect on students’ attitudes of mole concept. The researcher recommends that the use of constructivist approach in teaching and learning chemistry at the Senior High School should be encouraged by Curriculum developers and education implementers for students should have a hands-on experience with mole concept in learning chemistry. Keywords: Constructivist, Mole Concept, Demonstration, Purposive sampling, Intervention